Individual oath-swearing and lying under peer pressure - Sorravich Kingsuwankul (Tinbergen Institute, 2023)
Previous studies have shown that an oath can reduce lying at an individual level. Can oaths reduce lying in groups, a context where the prevalence of lying is typically higher? Results from a lab experiment reveal that the impact of an oath on lying in a group context depends on the incentive structure. Oath reduces lying only when payoffs are independent. Evidence supports the notion that payoff interdependence creates pressure on individuals to conform to the group, crowding out the impact of oath on honest reporting. An implication is that to be effective in an organizational context, an oath intervention must be designed in strict connection with the incentive structures.
Keywords: C92; D71; D91; 330; Honesty oath; lying; group incentive; peer pressure; lab experiment